2006
DOI: 10.2478/s11687-006-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

DOT-ELISA and parasitological examination for diagnosis of Schistosoma mansoni infection in Nigeria

Abstract: SummarySchistosoma mansoni infection constitutes significant economic and public health consequences. Accurate diagnosis of the infection is imperative in order to identify subjects needing care in the broadest sense. In this study the dot-ELISA and direct parasitological method were compared in the diagnosis of S. mansoni infection in Jos, Nigeria. Of the 106 subjects studied 64.2 % were S. mansoni positive serologically while only 10.4 % of them were found to have the parasite's egg in their stools. Individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The fi ndings of the current study also showed that participants aged 20 -40 years were signifi cantly more prone to be infected than younger and older ones. This result was in agreement with previous reports worldwide ( Raja'a et al, 2000;Gryseels et al, 2006;Mafuyai et al, 2006;Matthys et al, 2007;Ugbomoiko et al, 2010;Deribe et al, 2011). This could be explained by the excessive mobility of people at this age and they may become more exposed to infected water while swimming/playing or fetching water for domestic purposes or helping in agriculture activities.…”
Section: Discussionsupporting
confidence: 83%
“…The fi ndings of the current study also showed that participants aged 20 -40 years were signifi cantly more prone to be infected than younger and older ones. This result was in agreement with previous reports worldwide ( Raja'a et al, 2000;Gryseels et al, 2006;Mafuyai et al, 2006;Matthys et al, 2007;Ugbomoiko et al, 2010;Deribe et al, 2011). This could be explained by the excessive mobility of people at this age and they may become more exposed to infected water while swimming/playing or fetching water for domestic purposes or helping in agriculture activities.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, [52] observed higher frequency of contact in young children who indulged in watering of cattle, washing and bathing. In contrast, [7,53,54] observed that the 20-30year olds had more contact while washing, practicing irrigation farming, fetching water for daily routine household chores, fermentation of cassava tubers or even recreation.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa alone, about 90% of the 207 million infected cases have been reported while in Nigeria, up to 101 million persons are at risk of schistosomiasis with nearly 29 million infected in 2008 [6,7,8]. Many people suffer from schistosomiasis, which can cause hypertension, seizures, urinary obstruction, organ damage or destruction and death.…”
Section: Introductionmentioning
confidence: 99%